Assessing the quality of multimedia learning training programs for islamic school teachers through the CIPP evaluation model - Arsyil Waritsman; Tanwey Gerson Ratumanan; Patrisius Rahabav (12 Waiheru, 2026)
This study aims to analyze the quality of the multimedia learning training program organized by the Balai Diklat Keagamaan Ambon. The analysis of the training program's quality was conducted using the CIPP evaluation model. The method used in this study was a mixed-methods approach. Data were collected through observation and document analysis of the Context, Input, Process, and Product aspects of the multimedia learning training program. The collected data were then analyzed using a rubric adapted from the training quality index instrument developed by the Research and Development and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia. The results of the study indicate that (1) The Context Aspect of the multimedia learning training falls into the very high quality category and is in accordance with the needs and characteristics of Islamic school teachers; (2) The Input Aspect of the multimedia learning training falls into the very high quality category which is reinforced by information on the adequacy of human resources, curriculum and facilities and infrastructure; (3) The Process Aspect of the multimedia learning training falls into the very high quality category, which is reinforced by information on the learning Process and the evaluation Process that runs systematically and comprehensively; and (4) The Product Aspect of the training falls into the very high quality category, but the scope of the evaluation on the Product aspect is still limited to short-term results so that further evaluation is needed on the Product aspect that focuses on long-term results in the form of the impact of the training on alumni. Overall, the results of this study provide theoretical contributions to strengthening program evaluation models and practical contributions as a basis for policymaking and training program development within the Ministry of Religious Affairs. To ensure the program's sustainability and effectiveness, follow-up is needed through long-term impact evaluation and strengthened post-training monitoring mechanisms, so that the training's benefits can be optimally internalized into learning practices at the Islamic school.